2002
DOI: 10.1023/a:1015511908710
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This paper is the first of its kind to study the impact of Fabry disease (FD) in affected males, and shows that FD is associated with a significant decline in several domains. Using the medical outcomes study (MOS) SF-36 and a FD-specific questionnaire, we compared the observations found among these patients with that obtained for the general US population and other chronic disease states, including Gaucher disease (GD) (another lysosomal storage disorder), end-stage renal disease, stoke and AIDS. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…expectation of decreasing health). The SF-36 outcomes reported here are in accordance with earlier reports that demonstrated a decreased quality of life for male and female Fabry patients [26,27]. Because of the small sample size and wide confidence intervals, caution should be taken in interpreting these results, as the SF-36 differences before and during the shortage were rather small.…”
Section: Discussionsupporting
confidence: 89%
“…expectation of decreasing health). The SF-36 outcomes reported here are in accordance with earlier reports that demonstrated a decreased quality of life for male and female Fabry patients [26,27]. Because of the small sample size and wide confidence intervals, caution should be taken in interpreting these results, as the SF-36 differences before and during the shortage were rather small.…”
Section: Discussionsupporting
confidence: 89%
“…The small number of studies published before the widespread use of enzyme replacement therapy reported reduced QOL among FD patients, and the authors of those reports suggested that effective treatment with an appropriate agent would have great potential for improving QOL in patients with FD. 18 , 19 Our data on the activities of FD beneficiaries appear to show improvement in the clinical course of FD patients after the start of therapy.…”
Section: Discussionmentioning
confidence: 61%
“…Due to the X-linked inheritance, the disease primarily affects males, but females can be affected as well [4], [5], [6], [7] and both sexes can display symptoms during childhood [8], [9], [10], [11], [12]. The most frequent symptoms complained by pediatric patients with FD are episodes of recurrent pain in hands and feet (acroparesthesias), and gastrointestinal symptoms (mainly abdominal pain and diarrhea), manifestations that interfere with child's well-being and school performance and have a severe impact on quality of life (QoL) [8], [12], [13]. With age, progressive damage to vital organ systems develops in both genders [14], leading to multi-organ failure and even more reducing QoL [13] although the clinical expression of the disease has a wide inter- and intra-familial variability [15].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent symptoms complained by pediatric patients with FD are episodes of recurrent pain in hands and feet (acroparesthesias), and gastrointestinal symptoms (mainly abdominal pain and diarrhea), manifestations that interfere with child's well-being and school performance and have a severe impact on quality of life (QoL) [8], [12], [13]. With age, progressive damage to vital organ systems develops in both genders [14], leading to multi-organ failure and even more reducing QoL [13] although the clinical expression of the disease has a wide inter- and intra-familial variability [15]. Additionally, end-stage renal disease and life-threatening cardiovascular or cerebrovascular complications limit life-expectancy [16], [17].…”
Section: Introductionmentioning
confidence: 99%